Problems of Enhancing the Protection Mechanism for Citizens' Rights and Freedoms in the Decisions of the Constitutional Court of the Republic of Kazakhstan - Rakhmetulina, B.S.; Baimakhanova, D.M.; Rakhmetulin, A.B. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
The article examines the problems of enhancing the mechanism for protecting citizens’ rights and freedoms in the decisions and practice of the Constitutional Court of the Republic of Kazakhstan, focusing on both institutional development and societal factors influencing constitutional protection. The research addresses the central problem of insufficient effectiveness of constitutional safeguards, which is significantly affected by legal nihilism, low legal culture, and gaps in legislation that limit the full realization of constitutional rights. The object of the study is the system of constitutional protection of human and civil rights in Kazakhstan, while the subject is the functioning of the Constitutional Court, its jurisprudence, and the socio-legal conditions that determine the quality of constitutional justice. The study establishes that the majority of constitutional appeals in Kazakhstan arise from citizens’ legal illiteracy and misunderstandings regarding the Court’s jurisdiction. The Constitutional Court’s practice reveals numerous legislative inconsistencies in the areas of social protection, access to information, public service, and business regulation, demonstrating the urgent need for improved legal monitoring and more effective procedural mechanisms. The article concludes that strengthening legal education, increasing public awareness, and enhancing institutional guarantees of constitutional review are essential for ensuring the supremacy of the Constitution and improving access to justice.